Meal composition influences postprandial sensations independently of valence and gustation. Issue 8 (25th March 2018) - Pribic, T.; Vilaseca, H.; Nieto, A.; Hernandez, L.; Monrroy, H.; Malagelada, C.; Accarino, A.; Roca, J.; Azpiroz, F.
Abstract: Background: Palatability of meals with identical composition has been shown to influence postprandial sensations. Our aim was to determine to what extent meal composition influences postprandial sensations independently of palatability. Methods: Randomized, crossover, double‐blind trial comparing the postprandial responses to a low‐fat vs a high‐fat test meal, with the same physical and organoleptic characteristics (taste, smell, texture, color, and temperature). The test meal consisted in 150 g hummus containing either 17.7 g fat (low‐fat) or 22.3 g fat (high‐fat), 19.8 g toasts, 120 mL water and 50 g apple puree. In 12 non‐obese healthy men, palatability, homeostatic sensations (hunger/satiety, fullness) and hedonic sensations (digestive well‐being, mood) were measured on 10 cm scales before and during the 60‐min postprandial period. Comparisons between meals were performed with a two‐way repeated measures ANCOVA with premeal data as co‐variate. Key Results: Both test meals were rated equally palatable (palatability scores 3.8 ± 0.3 low‐fat, 3.3 ± 0.2 high‐fat; P = .156). As compared to the high‐fat meal, the low‐fat meal induced more satisfaction (meal effect on well‐being F (1, 21) = 4.92; P = .038) and tended to improve mood (meal effect F (1, 21) = 3.02; P = .064), and this was associated with a non‐significant decrease in satiety (meal effect F (1, 21) = 2.29; P = .145) and fullness (meal effect F (1, 21) = 1.57; P = .224). Conclusions and Inferences: The composition of meals with equal palatability influences postprandial satisfaction, even without significant impact on homeostatic sensations, although an effect on homeostatic sensations has not been excluded. These conditioning factors may have clinical implications in patients with impaired meal tolerance or meal‐related symptoms. Abstract : Effect of meal composition on the postprandial experience. As compared to the high‐fat meal, the low‐fat meal induced more digestive well‐being and increase in mood without significant differences in homeostatic sensation. Sensations were scored on 10 cm scales. P ‐values of main meal‐effect by two‐way repeated measures ANCOVA shown; dependent variable: postprandial scores; covariate: premeal scores. Temporal responses to meal ingestion analyzed by one‐way ANOVA for repeated measures; asterisks indicate significant differences from premeal values by post hoc comparisons ( P < .05 applying the Sidak correction procedure for multiple comparisons).